Dental caries and fissure sealant prevalence in first permanent molars among school boys aged 9 to 12 in Riyadh city, Kingdom of Saudi Arabia - Almajed, Ibrahim M.; Alomran, Ibrahim H.; Alkharji, Faisal I.; Binakresh, Abdulrahman I.; Almutairi, Abdulhakim M.; Alhabeeb, Khaled M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Dental caries is a major global public health concern. This study assessed dental caries prevalence and the use of fissure sealants on first permanent molars among Saudi Arabian boys aged 9–12 attending elementary schools to establish effective caries prevention strategies. Methods: Cluster probability sampling was employed to select public and private male elementary schools from five distinct geographic regions in Riyadh city, KSA; 601 male students in the fourth grade (aged 9–10 years), fifth grade (aged 10–11 years), and sixth grade (aged 11–12 years) were included. Only the first permanent molars’ occlusal surfaces were evaluated. Data management was performed using Microsoft excel, statistical analyses were conducted using the statistical package for the social sciences (SPSS), and the chi-square test was utilized. Results: The outcome demonstrated that 67.7% (n=407 children) had decayed, missing, or filled first permanent molars, indicating the presence of caries, while 32.3% (n=194) had caries-free first permanent molars. Only 6.8% (n=41) of children had received fissure sealants. At the tooth level, 37.7% (n=906) of examined teeth had decayed, and 8.1% (n=194) had fillings. The utilization rate of fissure sealants remained low at 3.9% (n=93), with 50.4% (n=1211) of first permanent molars remaining intact. Conclusions: This cross-sectional study highlights a significant prevalence between caries and the limited utilization of fissure sealants on first permanent molars among Saudi Arabian boys, underscoring the urgent need for proactive preventative measures and educational initiatives.